2015
DOI: 10.1920/wp.cem.2015.0915
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stochastic volatility models by nonparametric filtering

Abstract: A new estimation method of stochastic volatility models is proposed based on the nonparametric …lter of the instantaneous volatility process of Kristensen (2008). We use standard estimation methods for fully observed di¤usion processes but with the …ltered volatility process replacing the latent process. Our estimation strategy is applicable to both parametric and nonparametric stochastic volatility models, and we give theoretical results for both. The proposed estimators will carry biases due to the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Non-additive random utility models have been studied extensively in Apesteguia and Ballester (2014) and Kristensen, Nesheim, and de Paula (2015). These models are relevant in a wide range of settings, in particular those involving (waiting) time.…”
Section: Examplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Non-additive random utility models have been studied extensively in Apesteguia and Ballester (2014) and Kristensen, Nesheim, and de Paula (2015). These models are relevant in a wide range of settings, in particular those involving (waiting) time.…”
Section: Examplesmentioning
confidence: 99%
“…This literature goes back at least to Gale and Nikaido (1965), who showed that a differentiable function is injective if its domain is rectangular and its Jacobian is everywhere a P -matrix. Following the results of Gale and Nikaido (1965), Chiappori and Komunjer (2009) and Kristensen, Nesheim, and de Paula (2015) imposed assumptions on the functional form and support to ensure invertibility in multinomial choice and nonadditive random utility models. The main limitation of applying Gale and Nikaido (1965)'s result is that these restrictions (on differentiability, support, and the Jacobian) are often violated and/or are difficult to check.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations